2015
DOI: 10.1039/c5ra19014b
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity related, mechanistic, and modeling studies of gallotannins containing a glucitol-core and α-glucosidase

Abstract: Gallotannins containing a glucitol core, which are only produced by members of the maple (Acer) genus, are more potent α-glucosidase inhibitors than the clinical drug, acarbose. While this activity is influenced by the number of substituents on the glucitol core (e.g. more galloyl groups leads to increased activity), the mechanisms of inhibitory action are not known. Herein, we investigated ligand-enzyme interactions and binding mechanisms of a series of ‘glucitol-core containing gallotannins (GCGs)’ against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 57 publications
4
29
0
Order By: Relevance
“…The data fit well with the sum of single exponential decays with χ 2 values close to 1.00. As shown in Figure , the fluorescence lifetime of BHb presents no obvious changes under different concentrations of both CPFX and ENFX, which confirms that the quenching mode of BHb fluorescence caused by 2 FQs could be attributed to the static one, meaning the formation of the FQ − BHb complex …”
Section: Resultsmentioning
confidence: 55%
“…The data fit well with the sum of single exponential decays with χ 2 values close to 1.00. As shown in Figure , the fluorescence lifetime of BHb presents no obvious changes under different concentrations of both CPFX and ENFX, which confirms that the quenching mode of BHb fluorescence caused by 2 FQs could be attributed to the static one, meaning the formation of the FQ − BHb complex …”
Section: Resultsmentioning
confidence: 55%
“…The outstanding activity against ␣-glucosidase could be due to the presence of tannins and flavonoids since hydrolysable tannins and flavonoids generally show effective inhibition on ␣-glucosidase activity (Li et al, 2009; Ma et al, 2015;Zhang et al, 2015b). Li and colleagues found that vitexin and isovitexin were the major ␣-glucosidase inhibitors in Hawthorn leaves, which indicated stronger inhibition than acarbose with the IC 50 value of 25.11, 23.26 and 228.16 M, respectively (Li et al, 2009).…”
Section: Anti-hyperglycemic Activitymentioning
confidence: 92%
“…However, synthetic inhibitors, such as acarbose and miglitol, have serious undesirable adverse effects, such as flatulence, diarrhea and serious hepatitis (Carrascosa et al, 1997;Diaz-Gutierrez et al, 1998). At this point, effective, non-toxic and inexpensive ␣-glucosidase inhibitors derived from plant sources were reported to be more acceptable to consumers, and the significance is increasing all over the world (Kalra, 2014;Ma et al, 2015;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…27,28 Maplexin J (MJ; contains 4 galloyls) was synthesized in our laboratory as previously reported. 39 The structures of the GCGs are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%